Analisis Keputusan Pembelian yang dilihat dari Harga, Kualitas Pelayanan dan Promosi pada Pasar Tradisional dan Toko Swalayan - Sinollah; Fenti Wulandari (Jurnal Bisnis Islam dan Kewirausahaan, 2023)
The background of this research is because the traditional market and Toko Kita have decreased in the number of consumers, the longer the market is getting quieter so the authors want to know whether price, service quality and promotion affect purchasing decisions at traditional markets and Toko Kita in Pringu Village. Methods of data collection using questionnaires, interviews, observation and documentation. The population used are traders and visitors at traditional markets and at "Toko Kita" provided that they have shopped at the place at least once. Respondents in this study were 100 people with the provisions of simple random sampling. The data analysis technique uses validity, reliability, classical assumptions, multiple linear regression, coefficient of determination (R2), t test and F test using the help of SPSS version 24. The results of this study indicate that price and service quality affect purchasing decisions. while promotion has no effect on purchasing decisions at traditional markets and supermarkets "Toko Kita"